Virtual reconstruction of the Kebara 2 Neanderthal pelvis. Issue 151 (February 2021) - Adegboyega, Mayowa T.; Stamos, Peter A.; Hublin, Jean-Jacques; Weaver, Timothy D.
Abstract: The paucity of well-preserved pelvises in the hominin fossil record has hindered robust analyses of shifts in critical biological processes throughout human evolution. The Kebara 2 pelvis remains one of the best preserved hominin pelvises, providing a rare opportunity to assess Neanderthal pelvic morphology and function. Here, we present two new reconstructions of the Kebara 2 pelvis created from CT scans of the right hip bone and sacrum. For both reconstructions, we proceeded as follows. First, we virtually reconstructed the right hip bone and the sacrum by repositioning the fragments of the hip bone and sacrum. Then, we created a mirrored copy of the right hip bone to act as the left hip bone. Next, we 3D printed the three bones and physically articulated them. Finally, we used fiducial points collected from the physically articulated models to articulate the hip bones and sacrum in virtual space. Our objectives were to (1) reposition misaligned fragments, particularly the ischiopubic ramus; (2) create a 3D model of a complete pelvis; and (3) assess interobserver reconstruction variation. These new reconstructions show that, in comparison with previous measurements, Kebara 2 possessed a higher shape index (maximum anteroposterior length/maximum mediolateral width) for the pelvic inlet and perhaps the outlet and a more anteriorly positioned sacral promontory and pubic symphysis relative to the acetabula. The latter differences result in a lower ratio between the distances anterior and posterior to the anterior margins of the acetabula. Generally, the new reconstructions tend to accentuate features of the Kebara 2 pelvis––the long superior pubic ramus and anteriorly positioned pelvic inlet––that have already been discussed for Kebara 2 and other Neanderthals.